2017
DOI: 10.1016/j.jvs.2016.10.114
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of infrainguinal bypass surgery in patients with and without prior revascularization

Abstract: Objective Although an increasing number of patients with peripheral arterial disease undergo multiple revascularization procedures, the effect of prior interventions on outcomes remains unclear. The purpose of this study was to evaluate perioperative outcomes of bypass surgery in patients with and those without prior ipsilateral treatment. Methods Patients undergoing non-emergent infrainguinal bypass between 2011 and 2014 were identified in the NSQIP-Targeted Vascular module. After stratification by symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…In the proposed classification focusing on IC only, a grading was created based on their clinical consequences. After clustering severe IC grades 2-6, it was demonstrated that patient-related factors such as previous vascular surgery [11], anemia [12], and procedure-related factors such as the extent of the surgery [13] indeed had an impact on IC grade. Although a floor effect, which generally indicates the coarseness of a classification system, was observed in the system, it could be expected that the majority of these patients would not suffer from IC.…”
Section: Discussionmentioning
confidence: 99%
“…In the proposed classification focusing on IC only, a grading was created based on their clinical consequences. After clustering severe IC grades 2-6, it was demonstrated that patient-related factors such as previous vascular surgery [11], anemia [12], and procedure-related factors such as the extent of the surgery [13] indeed had an impact on IC grade. Although a floor effect, which generally indicates the coarseness of a classification system, was observed in the system, it could be expected that the majority of these patients would not suffer from IC.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies did not have information on the type of endovascular intervention performed, as the patients were often referred from peripheral hospitals without accompanying documentation or represented data obtained from multiple institutions. 16,18,20,26,27 The reporting of major adverse limb events (MALE) has been recommended by the Society for Vascular Surgery (SVS) Objective Performance Goals (OPG) Working Group specifically for use in critical trials involving patients with CLI and has been endorsed by both the SVS and the Food and Drug Administration. 32,33 MALE, which includes major above ankle amputation, new bypass, jump graft/interposition graft, graft occlusion, or major re-intervention requiring thrombectomy or thrombolysis, was infrequently reported and inconsistently described in the studies.…”
Section: Primary Bypass Bypass After Failed Evt Odds Ratio Weight M-hmentioning
confidence: 99%
“…Others have argued that failure of any intervention may result from systemic effects such as latent hypercoagulability, propensity for neointimal hyperplasia, or aggressive atherosclerosis. 18,26,34,35 However, not all the data support this as Nolan et al found that prior contralateral revascularisation was not a risk factor for worse outcomes following subsequent bypass, indicating that local factors (conduit, runoff, distal target) are probably more important. 26 The presence of marginal vein quality at the time of the initial revascularisation has also been implicated, as this may lead an interventionalist to favour an initial endovascular procedure but limits the options for subsequent autogenous bypass.…”
Section: Primary Bypass Bypass After Failed Evt Odds Ratio Weight M-hmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these open surgical procedures could represent a segment of the patient pool that after previous endovascular failures, have now opted for open surgery to treat their LLC [24].…”
Section: Businesswirecom/news/home/20171213005336/en/pq-bypass-mentioning
confidence: 99%